Six different football shoes, one playing surface and the weather; Assessing variation in shoe-surface traction over one season of elite football - Thomson, A.; Whiteley, R.; Wilson, M.; Bleakley, C. (PLOS ONE, 2019)
Introduction: An optimal range of shoe-surface traction (grip) exists to improve performance and minimise injury risk. Little information exists regarding the magnitude of traction forces at shoe-surface interface across a full season of elite football (soccer) using common football shoes. Objective: To assess variation in shoe-surface traction of six different football shoe models throughout a full playing season in Qatar encompassing climatic and grass species variations. Methods: Football shoes were loaded onto a portable shoe-surface traction testing machine at five individual testing time points to collect traction data (rotational and translational) on a soccer playing surface across one season. Surface mechanical properties (surface hardness, soil moisture) and climate data (temperature and humidity) were collected at each testing time point. Results: Peak rotational traction was significantly different across shoe models (F = 218, df = 5, p <0.0001), shoe outsole groups (F = 316.2, df = 2, p < .0001), and grass species (F = 202.8, df = 4, p < 0.0001). No main effect for shoe model was found for translational traction (F = 2.392, p = 0.07). Conclusions: The rotational (but not translational) traction varied substantially across different shoe types, outsole groups, and grass species. Highest rotational traction values were seen with soft ground outsole (screw-in metal studs) shoes tested on warm season grass. This objective data allows more informed footwear choices for football played in warm/hot climates on sand-based elite football playing surfaces. Further research is required to confirm if these findings extend across other football shoe brands.